(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The aim of the paper is to determine the potential of energy-efficiency in the production of the -wood resources. The beginning of the paper provides a short review of the existing situation as well as a list of main problems in wood resource usage in the power industry of Latvia. A special attention is paid to large amounts of fuelwood exports. The paper gives information on the potential of fuelwood and its distribution.The result of the research is the calculation ofpotential wood resource savings resulting from energy-efficiency increase activities in heat sources, heating mains and consumer systems, which are already run using fuelwood. As a result of energy-efficiency activities in the heat energy production process, it is possible to save up to even 4.2 million MWh of wood fuel.At the end, approximate calculations of emission savings in case of the utmost efficient wood usage have been carried out.